1986
DOI: 10.1097/00000542-198603000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Tracheo-bronchial Angles in Infants and Children

Abstract: REPLY Ventilation in patients with tracheal obstruction can create serious problems, particularly when the cross-sectional diameter of the trachea is narrowed to 5-6 mmHg. That is why the anaesthetic management and method of ventilation in our patient followed a step-by-step algorithm to ensure safety. The anaesthetic plan started by awake tracheal intubation, to be followed by spontaneous inhalation anaesthesia in 100% oxygen. Neuromuscular blockade and controlled ventilation were initiated after ensuring ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…They calculated the mean carinal angle that corresponds to SCA in our study, as 71° in children age 3 years and younger and 67° in children age over 3 years which were smaller than our calculations but also showed a decrease by aging as seen in our study. Unlike Tahir et al [7] we found that RBAs got narrower as the age increases which correlates with most findings in the literature [5,16,17]. According to this finding we can say that RBA gets much narrower than LBA and approaches to midline by aging.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…They calculated the mean carinal angle that corresponds to SCA in our study, as 71° in children age 3 years and younger and 67° in children age over 3 years which were smaller than our calculations but also showed a decrease by aging as seen in our study. Unlike Tahir et al [7] we found that RBAs got narrower as the age increases which correlates with most findings in the literature [5,16,17]. According to this finding we can say that RBA gets much narrower than LBA and approaches to midline by aging.…”
Section: Discussionsupporting
confidence: 83%
“…But their study included both children and adults and they did not classify children according to their age. Kubota et al [16] measured the angles in children with different age. They included children between 0–13 years of age and they classified the children into two groups as intubation group and non-intubation group and observed a little difference in RBA and LBA in all ages sum of which makes tracheal bifurcation angle (SCA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The left mainstem bronchus arises from the trachea at a 45-50 8 angle, whereas the right mainstem bronchus is a relatively straight extension of the trachea (36), and thus more subject to microaspiration. Compared with the RML, which abuts the diaphragm, the RUL is more proximal to the URT source community by the length of the bronchus intermedius (2-3 cm).…”
Section: Discussionmentioning
confidence: 99%